2016
DOI: 10.1017/s0261444816000069
|View full text |Cite
|
Sign up to set email alerts
|

Crossing borders, addressing diversity

Abstract: This paper presents a story of applied linguistics from my personal vantage point as a multilingual scholar whose career began outside the centers of research and scholarship. The article explains the assumptions and practices characterizing the foundation of the discipline in modernist discourses, and delineates the changes resulting from globalization towards postmodern discourses that question positivistic inquiry and homogeneity. As applied linguistics evolves to address diversity as the norm, the article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…1 Both such efforts have been salutary in countering deficit notions of the language practices of minoritized groups and in countering the treatment of members of those groups as somehow cognitively deficient in light of differences in their language practices. But those efforts have been founded on assumptions about languages, relations between languages, and relations between languages and their users that scholarship in these fields and in the contributing and intersecting fields of bilingualism, English as a lingua franca, World Englishes, intercultural rhetoric, sociolinguistics, and second language acquisition is increasingly calling into question (Baker 2013;Belcher 2014;Blommaert 2010;Calvet 1999Calvet , 2006Canagarajah 2011Canagarajah , 2016Firth and Wagner 1997;Heller 2007;Khubchandani 1998;Leung 2005Leung , 2013Leung , Harris, and Rampton 1997;Matsuda 1997;Parakrama 1995;Pennycook 2010). In a critique of these assumptions, Bruce Horner and John Trimbur have observed that composition courses themselves emerged out of a chain of reifications of language, social identities, and the links between them whereby individuals are assumed to have only a single social identity tied to a single language (e.g., "Chinese"), competence with which develops in a linear fashion toward mastery (Horner and Trimbur 2002, 596).…”
mentioning
confidence: 99%
“…1 Both such efforts have been salutary in countering deficit notions of the language practices of minoritized groups and in countering the treatment of members of those groups as somehow cognitively deficient in light of differences in their language practices. But those efforts have been founded on assumptions about languages, relations between languages, and relations between languages and their users that scholarship in these fields and in the contributing and intersecting fields of bilingualism, English as a lingua franca, World Englishes, intercultural rhetoric, sociolinguistics, and second language acquisition is increasingly calling into question (Baker 2013;Belcher 2014;Blommaert 2010;Calvet 1999Calvet , 2006Canagarajah 2011Canagarajah , 2016Firth and Wagner 1997;Heller 2007;Khubchandani 1998;Leung 2005Leung , 2013Leung , Harris, and Rampton 1997;Matsuda 1997;Parakrama 1995;Pennycook 2010). In a critique of these assumptions, Bruce Horner and John Trimbur have observed that composition courses themselves emerged out of a chain of reifications of language, social identities, and the links between them whereby individuals are assumed to have only a single social identity tied to a single language (e.g., "Chinese"), competence with which develops in a linear fashion toward mastery (Horner and Trimbur 2002, 596).…”
mentioning
confidence: 99%
“…1 Both such efforts have been salutary in countering deficit notions of the language practices of minoritized groups and in countering the treatment of members of those groups as somehow cognitively deficient in light of differences in their language practices. But those efforts have been founded on assumptions about languages, relations between languages, and relations between languages and their users that scholarship in these fields and in the contributing and intersecting fields of bilingualism, English as a lingua franca, World Englishes, intercultural rhetoric, sociolinguistics, and second language acquisition is increasingly calling into question (Baker 2013;Belcher 2014;Blommaert 2010;Calvet 1999Calvet , 2006Canagarajah 2011Canagarajah , 2016Firth and Wagner 1997;Heller 2007;Khubchandani 1998;Leung 2005Leung , 2013Leung , Harris, and Rampton 1997;Matsuda 1997;Parakrama 1995;Pennycook 2010). In a critique of these assumptions, Bruce Horner and John Trimbur have observed that composition courses themselves emerged out of a chain of reifications of language, social identities, and the links between them whereby individuals are assumed to have only a single social identity tied to a single language (e.g., "Chinese"), competence with which develops in a linear fashion toward mastery (Horner and Trimbur 2002, 596).…”
mentioning
confidence: 99%
“…in light of differences in their language practices. But those efforts have been founded on assumptions about languages, relations between languages, and relations between languages and their users that scholarship in these fields and in the contributing and intersecting fields of bilingualism, English as a lingua franca, World Englishes, intercultural rhetoric, sociolinguistics, and second language acquisition is increasingly calling into question (Baker 2013;Belcher 2014;Blommaert 2010;Calvet 1999Calvet , 2006Canagarajah 2011Canagarajah , 2016Firth and Wagner 1997;Heller 2007;Khubchandani 1998;Leung 2005Leung , 2013Leung , Harris, and Rampton 1997;Matsuda 1997;Parakrama 1995;Pennycook 2010). In a critique of these assumptions, Bruce Horner and John Trimbur have observed that composition courses themselves emerged out of a chain of reifications of language, social identities, and the links between them whereby individuals are assumed to have only a single social identity tied to a single language (e.g., "Chinese"), competence with which develops in a linear fashion toward mastery (Horner and Trimbur 2002, 596).…”
mentioning
confidence: 99%